Assessing the conservation status of and challenges facing Asiatic black bears and Malayan sun bears in Bangladesh - Muntasir Akash; Haris Debbarma; Sultan Ahmed; Amarta Galib Chowdhury; Tania Zakir; Khondokar Newaz M.D. Sarafat; Sandeep Sharma (Oryx)
South of 25°N, the rugged, riparian, mixed evergreen forests of eastern Bangladesh mark the western edge of the ranges of the globally Vulnerable Asiatic black bear Ursus thibetanus and sun bear Helarctos malayanus. According to the IUCN Red List, the distribution of bears in Bangladesh is unclear: black bears are described as ‘scattered’ and ‘likely to be very low in number’ and sun bears as ‘vagrants’ entering from the adjoining north-east Indian forests. These statements are not based on any population or habitat assessments, impeding focused research and conservation investment. We compiled recent evidence of bear presence in Bangladesh based on camera trapping, literature reviews and analysis of media reports. From peer-reviewed and grey literature published during 2010–2022 we traced 43 verifiable accounts of black bears in the country. Our camera-trap survey in Rajkandi Reserve Forest produced the first ever evidence of a small population of black bears in north-eastern Bangladesh. Two field studies (in 2016 and 2021) reported camera-trap observations and multiple incidents of poaching of sun bears in Kassalong Reserve Forest and Sangu-Matamuhuri Reserve Forest in south-eastern Bangladesh. Media reports on conflict incidents presented 83 human casualties (80 injured, three dead) and 13 bear casualties (six dead, seven rescued) during 2003–2023. The incidents peaked in the summer (17); 79% were reported during 2018–2023. Cognizant of the fact that the absence of evidence is not evidence of absence, our study calls for systematic conservation measures for both of these bear species in unprotected hill forests in eastern Bangladesh.